The memory of the War of the Pacific in Lima and the “Captive Provinces” (1884-1929): Between revanchism and patriotic heroism - Valle Vera, María Lucía (2025)
This study analyzes in a comparative way how the memory following the War of the Pacific was shaped in Lima and the provinces of Tacna and Arica, the “captive provinces,” between the years 1884 and 1929, thus encompassing the postwar time up to the signing of the Treaty of Lima (June 3, 1929), which resolved the outstanding issues between Peru and Chile. It explores the construction of national memory promoted from Lima and the memory of captivity in Tacna and Arica. Likewise, it offers a reflection on the relationship between memory and nationalism, as well as on the cultural manifestations associated with it.